2020
DOI: 10.1038/s41598-020-74734-1
|View full text |Cite
|
Sign up to set email alerts
|

Historical trend on seed amino acid concentration does not follow protein changes in soybeans

Abstract: Soybean [Glycine max (L.) Merr.] is the most important oilseed crop for animal industry due to its high protein concentration and high relative abundance of essential and non-essential amino acids (AAs). However, the selection for high-yielding genotypes has reduced seed protein concentration over time, and little is known about its impact on AAs. The aim of this research was to determine the genetic shifts of seed composition for 18 AAs in 13 soybean genotypes released between 1980 and 2014. Additionally, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 39 publications
(41 reference statements)
2
25
0
Order By: Relevance
“…Nevertheless, several pieces of evidence suggest that higher productivity neither boosted the content nor quality of protein of soybean seeds, since a negative correlation between yield and the protein content has been often reported (Assefa et al, 2018; de Borja Reis et al, 2020; Mello Filho et al, 2004). A recent study conducted with 26 soybean cultivars released over the last 50 years in southern Brazil revealed that the yield has increased at a rate of 45.9 kg ha−1 year -1 whereas the protein content has decreased by 0.84 g kg−1 year -1 , respectively (Umburanas et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, several pieces of evidence suggest that higher productivity neither boosted the content nor quality of protein of soybean seeds, since a negative correlation between yield and the protein content has been often reported (Assefa et al, 2018; de Borja Reis et al, 2020; Mello Filho et al, 2004). A recent study conducted with 26 soybean cultivars released over the last 50 years in southern Brazil revealed that the yield has increased at a rate of 45.9 kg ha−1 year -1 whereas the protein content has decreased by 0.84 g kg−1 year -1 , respectively (Umburanas et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…As these figures are affected by environmental conditions and crop management practices (Assefa et al, 2019; de Borja Reis et al, 2020), one should expect that the protein content in soybean seeds might surely be influenced by their elemental composition. In this scenario, direct relationships were observed between protein content and the sulphur concentration (p = 0.5), as well as zinc, copper (p > 0.1-0.2), and manganese concentration in the probed soybean seeds (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Changing the yield allocation among canopy portions could be manipulated by plant breeding and management practices. For instance, enhanced branching in modern genotypes could be related to stable LAA concentration despite protein decay over the last 40 years (de Borja Reis et al, 2020 ). Future research must consider to study the branching process (initiation, progress rate and duration, dry matter, and harvest index) as a potential moderator of soybean seed composition, plausibly benefitting human nutrition with improved AA profile and oil concentration.…”
Section: Discussionmentioning
confidence: 99%